Peran Puskesmas dalam Pengendalian ISPA di Wilayah Kerja Puskesmas Koya Kecamatan Tondano Selatan - Linda Dina Laelaem; Theo W. E. Mautang; Jilly Toar (Jurnal Ilmiah Kesehatan, 2025)
he purpose of this study is To describe the role of the Koya Health Center through health promotion in controlling ISPA in the work area of the Koya Health Center, South Tondano District To identify factors that influence clean and healthy behavior in the work area of the Koya Health Center, South Tondano District, Minahasa Regency To describe health promotion in the ISPA control program in the work area of the Koya Health Center, Tondane Ciatan District, Minahasa Regency. The type of research used in this study is a qualitative research type. This type of research is used to determine the role of the health center in preventing ISPA in the work area of the Koya Health Center, South Tondano District, Minahasa Regency. The results of this study indicate that the respondents I interviewed were two respondents, namely the Sapa program organizer and the head of the Koya Health Center. From the results of the interview with the health center, in one month they often carry out Poryandu Nanam for counseling about ISPA, usually only 2-3 times a day. sometimes just using posters or billboards.